The effect of transformational leadership on innovative work behavior: mediating role of knowledge sharing - Wulan Dari, Atikah; Tania, Ken Ditha; Wedhasmara, Ari; Meiriza, Allsela (MBR (Management and Business Review), 2023)
PLN, as Indonesiaâ€™s electricity utilities company, upholds AKHLAK values, where every employees must innovate in doing their work. The purpose of this research is to analyze the extent of the role of transformational leadership on innovative work behavior with knowledge sharing as the mediation variable. This research uses a quantitative approach with PLS-SEM modeling assisted with Smart-PLS application with 70 employees as respondents by distributed questionnaires.Â  The outcome implies that transformational leadership and knowledge sharing have a significant influence on innovative work behavior, as well as knowledge sharing partially mediates between transformational leadership and innovative work behavior. Future research is expected to discuss other leadership variables that are in accordance with the prevailing trends and wider research objects.